Sonic textualities in translation: the interlingual and transmodal trajectories of the musical play la cage aux folles - Villanueva-Jordán, Iván (2025)
This study examines four versions of “I Am What I Am,” penned by Jerry Herman for the 1983 musical La Cage aux Folles, a Broadway show notable for featuring two gay protagonists amid the conservative resurgence in the United States and the onset of the HIV epidemic. This analysis focuses on the composition and how the lyrics of the songs engage with discourses on sexuality. Employing a multimodal translation approach, this research underscores how the interplay between musical and linguistic systems, alongside the material elements of each version, facilitates the exploration of the trajectories of cultural artifacts in the shaping of queer imaginaries and archive.